Konsep Kerakyatan Dalam Filsafat Politik Ibnu Rusyd (Studi Kasus Di Desa Kadibolo Klaten) - emy, dwy (Universitas Islam Negeri Raden Intan Lampung, 2024)
Abstract;This research will discuss issues regarding democracy in the view of Ibn Rushd's political philosophy. He is one of the figures who discusses democracy. In this context, Ibnu Rushd puts forward democracy as a concept of independence and freedom. However, according to him, independence and liberty are not without regulatory actions, but freedom and freedom according to religious principles. Ibnu Rushd promoted the concept of democracy, a system which according to him was more in line with the basic laws of human nature. As a realization of the popular ideas he promoted, Ibnu Rushd offered the concept of sovereignty (as-Siyadah) which contained three basic popular principles, namely freedom or independence (al-Huriyyah), equality (al-Musawah), and diversity (pluralism). This research uses quantitative methods with data collection techniques and interviews with several people in Kadibolo village who apply the populist concept based on Ibnu Rushd's thoughts. The research findings are that in Kadibolo village itself, in running its government, it uses popular principles which give its people independence in expressing opinions and also in carrying out activities. However, this does not mean that independence frees them to act as they please, there are still applicable regulations that must be obeyed so that Kadbiolo village remains well organized.Keywords:Democracy; Freedom; Ibn Rushd; Politics. Abstrak;Penelitian ini akan membahas permasalahan mengenai kerakyatan dalam pandangan filsafat politik Ibnu Rusyd. Ia merupakan salah satu tokoh yang membahas tentang kerakyatan. Dalam konteks ini Ibnu Rusyd lebih mengemukkan kerakyatan sebagai konsep kemerdekaan dan kebebasan. Namun kemerdekaan dan kebebasan menurutnya bukanlah tanpa adanya perbuatan yang mengatur, akan tetapi merdeka dan bebas sesuai prinsip agama. Ibnu Rusyd mengusung konsep kerakyatan, sebuah sistem yang menurutnya lebih sesuai dengan hukum-hukum dasar fitriyah manusia. Sebagai realisasi ide kerakyatan yang diusungnya, Ibnu Rusyd menawarkan konsep kedaulatan (as-Siyadah) yang di dalamnya terkandung tiga prinsip dasar kerakyatan, yakni kebebasan atau kemerdekaan (al-Huriyyah), persamaan (al-Musawah), dan keberagaman (pluralisme). Penelitian ini menggunakan metode kuantitatif dengan teknik pengumpulan data dan wawancara beberapa orang di desa Kadibolo yang menerapkan konsep kerakyatan atas pemikiran Ibnu Rusyd. Temuan penelitian bahwa di desa Kadibolo sendiri dalam menjalankan pemerintahannya menggunakan prinsip kerakyatan yang memberikan kemerdekaan masyarakatnya dalam menyampaikan pendapat dan juga dalam berkegiatan. Akan tetapi bukan berarti kemerdekaan tersebut membebaskan mereka untuk bertindak semaunya, tetap ada peraturan yang berlaku untuk ditaati agar desa Kadbiolo tetap tertata dengan baik.Kata Kunci: Ibnu Rusyd; Kerakyatan; Kebebasan; Politik.